Could living space provision in the first lactation have long term effects on milk production in housed dairy cows? - Thompson, Jake S.; Hudson, Christopher D.; Green, Martin J. (Frontiers in Animal Science, 2026)
The productive life of a dairy cow centres milk production, reproduction, and health status. Current management practices, including living space provision, for first lactation animals are highly variable and associated with large impacts on reproduction and milk production. The aim of this investigation was to explore the potential lifetime effects on milk production when primiparous cows are provided with additional living space. This prospective study used two cohorts of cows from a previous randomised controlled trial that used matched pairs of cows, with one in each pair provided with 3m2 living space (“Control”) and the other 6.5m2 living space (“High”). In terms of lifetime milk production, the high space group consistently performed better; mean milk volume per lifetime day in the control space group was 37.55L versus 38.92L in the high space group. A random effects model was used to account for repeated measures within cow and revealed significant and substantially increased milk production in the high space group at less than 400 days in milk, between 800–1000 days in milk and greater than 1200 days in milk, compared the control space cohort. A Cox-Proportional hazards model was built to investigate time to herd exit, no difference was identified between the groups. This research allows cautious insights into the potential for the impact of increased space allowance for primiparous dairy cows on lifetime milk production. This could have important implications relating to societal perception, health, welfare, economics and environment impact, which could aid more sustainable approaches to managing dairy cows.